The aminoglycoside multi-acetylating activity of the enhanced intracellular survival (Eis) protein from Mycobacterium smegmatis and its inhibition - Chen, Wenjing (2012)
The enhanced intracellular survival (Eis) protein improves Mycobacterium smegmatis (Msm) survival in macrophages and functions as the acetyltransferase responsible for kanamycin A resistance, a hallmark of extensively drug-resistant (XDR) tuberculosis, in a large number of Mycobacterium tuberculosis (Mtb) clinical isolates. We recently demonstrated that Eis from Mtb (Eis_Mtb) efficiently multi-acetylates a variety of aminoglycoside (AG) antibiotics. Here, to gain insight into the origin of substrate selectivity of AG multi-acetylation by Eis, we analyzed AG acetylation by Eis_Msm, investigated its inhibition, and compared these functions to those of Eis_Mtb. Even though for several AGs the multi-acetylation properties of Eis_Msm and Eis_Mtb are similar, there are three major differences: (i) Eis_Msm di-acetylates apramycin, a conformationally constrained AG, which Eis_Mtb cannot modify, (ii) Eis_Msm tri-acetylates paromomycin, which can be only di-acetylated by Eis_Mtb, and (iii) Eis_Msm only mono-acetylates hygromycin, a structurally unique AG that is di-acetylated by Eis_Mtb. Several non-conserved amino acid residues lining the AG-binding pocket of Eis are likely responsible for these differences between the two Eis homologs. Specifically, we propose that because the AG-binding pocket of Eis_Msm is more open than that of Eis_Mtb, it accommodates apramycin for acetylation in Eis_Msm, but not in Eis_Mtb. We also demonstrate that inhibitors of Eis_Mtb that we recently discovered can inhibit Eis_Msm activity. These observations help define the structural origins of substrate preference among Eis homologs and suggest that Eis_Mtb inhibitors may be applied against all pathogenic mycobacteria to overcome AG resistance caused by Eis up-regulation.